2006
DOI: 10.1016/j.msea.2006.07.084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing on microstructure and properties of SLS Nylon 12

Abstract: There currently exists the requirement to improve reproducibility and mechanical properties of SLS Nylon parts for RRapid MManufacturing (RM). In order to achieve this, further fundamental research is needed and this paper addresses this need by investigating effects of potential sources of the lack of reproducibility (i.e. build procedure/parameters and powder blend) and reports effects in relation to crystal structure, microstructure, chemical structure (molecular weight) and mechanical properties.Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(173 citation statements)
references
References 9 publications
10
145
1
5
Order By: Relevance
“…Although the DSC is commonly used to quantify the melting behavior of samples in both melt processing 1,24,25 and powder sintering, 5,7,14,26 we found that the melting temperatures obtained from the DSC did not result in fully melted powders in HSM (see Fig. 1).…”
Section: Optimization Of Processing Conditions By Hot Stage Microscopymentioning
confidence: 91%
See 3 more Smart Citations
“…Although the DSC is commonly used to quantify the melting behavior of samples in both melt processing 1,24,25 and powder sintering, 5,7,14,26 we found that the melting temperatures obtained from the DSC did not result in fully melted powders in HSM (see Fig. 1).…”
Section: Optimization Of Processing Conditions By Hot Stage Microscopymentioning
confidence: 91%
“…7 The peak positions were just above 185°C with a variation <1°C. However, the melting temperature observed during HSM was different, revealing a much larger variation between neat PA12 and the two different composite powders, as shown in Fig.…”
Section: Optimization Of Processing Conditions By Hot Stage Microscopymentioning
confidence: 96%
See 2 more Smart Citations
“…Ti-6Al-4V also has a near perfectly plastic response (Rafi et al 2013), making it very suitable for use in conjunction with the suggested plastic optimization formulation (see Section 2.1). Polymer materials such as Nylon-12 can also be used but the material properties are very sensitive to process parameters and can be inconsistent between builds and machines (Vasquez et al 2011;Zarringhalam et al 2006).…”
Section: Choice Of Additive Manufacturing Processmentioning
confidence: 99%